Is 2‐Hydroxypropyl‐β‐cyclodextrin a Suitable Carrier for Central Administration of Δ9‐Tetrahydrocannabinol? Preclinical Evidence. Issue 8 (18th September 2017) - Agabio, R.; Sanna, F.; Lobina, C.; Monduzzi, M.; Nairi, V.; Cugia, F.; Mameli, S.; Pisanu, G. M.; Gessa, G. L.; Melis, M. R.
ABSTRACT: Preclinical Research Δ 9 ‐Tetrahydrocannabinol (THC) is a hydrophobic compound that has a potent antinociceptive effect in animals after intrathecal (IT) or intracerebroventricular (ICV) administration. The lack of a suitable solvent precludes its IT administration in humans. 2‐Hydroxypropyl‐β‐cyclodextrin (HPβCD) increases the water solubility of hydrophobic drugs and is approved for IT administration in humans. To investigate whether HPβCD might be a suitable carrier for ICV administration of THC in rats, two formulations containing THC complexed with HPβCD (30 and 135 μg of THC per animal) and vehicle were administered to Wistar rats. The antinociceptive effect (using the tail flick test), locomotor activity, and body temperature were evaluated. ICV injection of 135 μg of THC/HPβCD complex increased tail flick latency, reduced locomotor activity, and had a dual effect on body temperature. The 30 μg THC/HPβCD formulation only produced a hyperthermic effect. All animals appeared healthy, with no difference between the groups. These results were similar to those obtained in other preclinical studies in which THC was administered centrally using solvents that are unsuitable for IT administration in humans because of their toxicity. Our findings suggest that HPβCD may be a useful carrier for IT administration of THC in humans. Drug Dev Res 78 : 411‐419, 2017. © 2017 Wiley Periodicals, Inc.